PENGARUH PENGGUNAAN MULTIMEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA - Waruwu, Henoki (IKIP Gunungsitoli, 2008)
Abstcact: This research has purpose to know the effect of medias using toward students learning outcomes in genetics topic. These media consist of conventional, overhead projector, computer based media. This research suggest three conclusions: (1) overhead projector media using in instructional had increased students learning outcomes rather than conventional media, (2) computer based media using in instructional had increased students learning outcomes rather than both of conventional and overhead projector media.Kata kunci : Multimedia pembelajaran, hasil belajar genetika